Investigation of antibacterial and cytotoxic potential of phenolics derived from Cistus incanus L. by means of thin-layer chromatography-direct bioautography and cytotoxicity assay. Issue 6 (3rd April 2018) - Szeremeta, Dariusz; Knaś, Magdalena; Długosz, Ewa; Krzykała, Klaudia; Mrozek-Wilczkiewicz, Anna; Musioł, Robert; Kowalska, Teresa; Ott, Péter G.; Sajewicz, Mieczysław; Móricz, Ágnes M.
ABSTRACT: Cistus incanus L. (hairy rockrose) is a medicinal plant which belongs to the Cistaceae family and the Cistus genus, with a well established position in traditional medicine of the Mediterranean basin and the Middle East. It was the aim of this study to compare antibacterial activity of the phenolics derived from fourteen C. incanus samples of different origin (Turkey, Albania, Greece, and an unknown geographical location) obtained as herbal teas from a local market of diet supplements. This activity was assessed with the use of thin-layer chromatography–direct bioautography (TLC-DB) applied to crude extracts against the Gram negative naturally luminescent marine bacterium Aliivibrio fischeri and the Gram positive soil bacterium Bacillus subtilis as the test microorganisms. It was established that in spite of different origin of the investigated herbal samples, in qualitative terms their antibacterial activity was closely comparable and more strongly pronounced against the Gram positive than the Gram negative bacterium. Crude extract originating from one herbal specimen labelled A3 (sample no. 3 from Albania) underwent selective multi-step extraction of the phenolics, dividing them into six fractions (I toVI ) that expectedly contain flavonoid aglycons, free phenolic acids, non-polar flavonoid glycosides, polar flavonoid glycosides, and phenolic acids obtained through the acidic and basic hydrolysis from the respective glycosides. Antibacterial activity of each A3 fraction was then assessed with the use of the same TLC-DB approach and it was established that the strongest effect was exerted by fractionsI andII (flavonoid aglycons and free phenolic acids). Moreover, cytotoxic assay was performed for the crude C. incanus extracts against the human colon adenocarcinoma cells and a moderate yet well measurable cytotoxic effect was observed with all investigated C. incanus samples. In analogy to antibacterial activity, also in this case cytotoxic potential of all investigated crude C. incanus extracts was similar. GRAPHICAL ABSTRACT: